Transforming Adversity into Opportunity: Leveraging Sidoarjo's Volcanic Mud for Civil and Environmental Engineering - Amalia Kusuma Dewi; Bastian Okto Bangkit Sentosa; Sandyanto Adityosulindro (Journal of World Science, 2025)
The Sidoarjo volcanic mudflow disaster in East Java, which began in 2006, has caused ongoing environmental and socio-economic challenges. However, the volcanic mud’s unique composition, rich in silica (SiO?), alumina (Al?O?), and iron oxide (Fe?O?), presents significant potential for resource recovery. This review utilizes a Systematic Literature Review (SLR) approach, following the PRISMA 2020 guidelines, to analyze 49 relevant publications from 2013 to 2024. The findings indicate that treated Sidoarjo mud can be effectively utilized in various civil engineering applications, including ceramic tiles, concrete bricks, geopolymer binders, and road base stabilizers, fulfilling national performance standards while contributing to reduced carbon emissions and construction costs. Moreover, Sidoarjo mud demonstrates its value in environmental engineering, showing effectiveness as an adsorbent for heavy metals, dyes, and organic pollutants in water treatment, as well as serving as a catalyst support in biodiesel production. This review underscores the multidisciplinary value of Sidoarjo mud, positioning it as a key material in advancing circular economy practices and promoting environmentally sustainable innovations within the built environment.